3D Gerchberg-Saxton Optical Correlation - Wen Chen (IEEE Photonics Journal)
Since Gerchberg–Saxton algorithm was developed, it has been applied in various fields, e.g., optical display and optical tweezers. In this paper, three-dimensional (3D) Gerchberg–Saxton optical correlation is proposed. A 2D image is divided into particle-like points placed in 3D space, which are simultaneously encoded into the cascaded phase masks by using a modified Gerchberg–Saxton algorithm. The extracted phase masks can be flexibly compressed, and the decoded images can be verified via optical correlation. It is also illustrated that high security and high flexibility can be achieved by using the proposed 3D Gerchberg–Saxton correlation method. The proposed 3D Gerchberg–Saxton algorithm can provide a new and significant insight on optical correlation.